Numerical modeling of mesoscale vortex structures near a strong hot impurity source in atmosphere boundary layers - Shvarts, Konstantin Grigor'evich; Shklyaev, Vladimir Alexandrovich (Computational Continuum Mechanics, 2009)
This paper presents a new quasi two-dimensional model for impurity propagation from a strong thermal source (by example of oil ignition) taking into account the heterogeneity of turbulent diffusion above the source and outside of it. The equations are deduced from the three-dimensional model of convection. Boundary conditions and coefficients of the model are determined by small-scale turbulence parameterization techniques. The results of numerical calculations show that the intense vortex motion in the bottom layer of atmosphere is formed above the place of oil ignition due to the linear and nonlinear effects of the non-uniform horizontal temperature gradient near the thermal torch. The physical characteristics of vortices and their number are defined by the turbulent heat transfer factors outside of the heat source and above it. The wind field formed under these conditions has an essential influence on the character of oil impurity distribution in the vicinity of the heat source.